Factors affecting glycemic control and kidney function in type 2 diabetes mellitus patients in Yogyakarta - Ardhiani, Menit; Febrianti, Yosi; Ningrum, Vitarani Dwi Ananda; Wijaya, Diani Puspa (Jurnal Ilmiah Farmasi, 2026)
Background: Type 2 Diabetes Mellitus (Type 2 DM) is a metabolic disease whose prevalence continues to increase and can cause various complications, one of which is diabetic nephropathy, which can lead to kidney failure. Objective: To evaluate the association of sociodemographic and clinical factors of diabetic type 2 patients with HbA1c and eGFR.Methods: A cross-sectional study was conducted among 170 diabetic patients at community pharmacies in Yogyakarta from January 2022 to January 2023. Data were collected from patients' medication records, laboratory results of HbA1c, creatinine, eGFR, and structured questionnaires. A Chi-square test was performed to analyze group differences in categorical variables.Results: Duration of diabetes mellitus (p = 0.021), comorbid hypertension (p = 0.040), and diabetes medication therapy (p < 0.001) were associated with good HbA1c control. Serum creatinine levels were significantly associated with age (p < 0.001). Age (p < 0.001), BMI (p = 0.039), education (p = 0.022), duration of diabetes (p = 0.044), and hypertension comorbidity (p = 0.040) were the factors that affected eGFR. However, no significant correlation was found between HbA1c and serum creatinine (r = 0.114; p = 0.134) or between HbA1c and eGFR (r = 0.026; p = 0.739).Conclusion: There is no significant correlation between glycemic control (HbA1c) and renal function markers (serum creatinine and eGFR) in type 2 diabetic patients.